Genealogia dos poderes punitivos e aporias da justiça - Moreira, Marcela Henriques Mendes (2020)
This research aims to denounce the punitive powers that cross modern criminal justice and their violence in the guilty bodies. A genealogy of the punitive powers brings to the penal scene characters, contexts and important pieces for a critique of the condemnatory judgment. I am interested in the concrete effects produced by connected and expanded powers for the strategic and discriminating capture of certain social subjects, targets of punishment. I argue that the materialization of penalties does not aim at the effective repression of crime, it produces class and race sacrifices, in a hidden scene of legitimate violence. To think about justice, it is necessary to reveal and deconstruct the entire modern criminal scene, which strives to provide a corrective and universal justification for the application of the penalty, when, in practice, they condemn bare lives.